Effect and mechanism of reading habits on physical and mental health among the elderly: Evidence from China - Zhang, Wang; Zhang, Yu; Wang, Jie (Frontiers in Public Health, 2022)
Responding to an aging society worldwide and ensuring the physical and mental health of the elderly are important problems that need to be addressed. Thus, this study aimed to improve the quality of providing the spiritual and cultural needs of the elderly and study the internal transmission of reading habits and its effect on the physical and mental health of the elderly. Using the data from China's comprehensive social survey in 2018, this study applied the Probit model and ordinary least squares method to comprehensively estimate the influence of reading habits of the elderly on their physical and mental health. Stepwise regression and bootstrap method were combined to explore the influencing mechanism, and an instrumental variable method was used to solve endogeneity problems. Results indicate that the reading habits of the elderly have a significantly positive effect on their own physical and mental health. Social activity is the positive conduction path, whereas social justice perception and learning willingness are the negative conduction path. Among low-income families, agricultural workers, and the elderly whose household registration is in rural areas, the benefits of reading to the body and mind are more significant. After dealing with endogeneity problems and a series of robustness tests, the conclusion of this paper still holds. Finally, reference policy suggestions are proposed for the follow-up active aging policy, such as promoting reading for all, organizing various social activities, formulating active pension policies for the elderly, and allocating more public resources for vulnerable elderly groups.